Ceramic tile prepared from waste materials and preparation method thereof

By mixing and firing components such as discarded ceramic sheets, ceramic tiles with excellent strength and good mechanical properties are prepared, which solves the problems of low strength or poor toughness of existing ceramic products, and realizes the preparation of high-performance ceramic products .

CN119390424APending Publication Date: 2025-02-07JINJIANG MENGSHENG BUILDING MATERIALS CO LTD

Patent Information

Application Number
CN202411460592.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing ceramic products have low strength or poor toughness, which cannot meet consumers' high-performance demand for ceramic products, resulting in waste of resources.

Method used

By mixing discarded ceramic sheets, gel particles, precursor materials, carbon nanofibers, magnesium oxide, binder, cinder and kaolin, and then molding, degumming and sintering, it is prepared with excellent strength and good strength after ball milling. Mechanical properties of ceramic tiles.

Benefits of technology

It achieves high strength and good mechanical properties of ceramic tiles, meets consumers' high performance needs for ceramic products, and avoids waste of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The ceramic tile is prepared from the following components in parts by weight: 20 to 30 parts of waste ceramic chips, 30 to 40 parts of gel particles, 10 to 20 parts of a precursor material, 5 to 8 parts of carbon nanofibers, 6 to 8 parts of magnesium oxide, 10 to 12 parts of a binder, 10 to 15 parts of coal cinder and 18 to 20 parts of kaolin. According to the ceramic tile prepared from the waste materials and the preparation method of the ceramic tile, the prepared ceramic tile has excellent strength and good mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a ceramic tile made from waste materials and a preparation method thereof. Background Art

[0002] There are also formulas and preparation methods for ceramic products in the prior art. Although the ceramic products prepared according to these formulas and methods have a certain glossiness, there are problems with low strength or poor toughness of the ceramic products. For example, some existing ceramic products have low strength and low bearing capacity. With the development of the economy and the improvement of people's living standards, people have higher and higher requirements for the quality of life. Consumers have continuously improved their performance requirements for daily-use ceramics, sanitary ceramics and architectural ceramics. They not only require the products to be beautiful, but also require them to have density, strength, practicality and wear resistance. Ceramics that do not meet their needs and preferences will be eliminated unnecessarily and waste resources will be wasted. Therefore, how to use existing resources and waste ceramics to prepare high-quality ceramics is also an urgent problem to be solved. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a ceramic tile made from waste materials and a preparation method thereof, wherein the prepared ceramic tile has excellent strength and good mechanical properties.

[0004] In order to achieve the above object, the present invention provides the following technical solutions: A ceramic tile made from waste materials comprises the following components in parts by weight: 20-30 parts of waste ceramic pieces, 30-40 parts of gel particles, 10-20 parts of precursor materials, 5-8 parts of carbon nanofibers, 6-8 parts of magnesium oxide, 10-12 parts of binder, 10-15 parts of coal slag and 18-20 parts of kaolin.

[0005] Preferably, the binder is sodium hydroxymethyl cellulose.

[0006] A method for preparing ceramic tiles made from waste materials comprises the following steps: S1: Mix the waste ceramic pieces, gel particles, precursor materials, carbon nanofibers, magnesium oxide, binder, coal slag and kaolin, and ball-mill them through a 200-mesh sieve to obtain a mixture; S2: The mixed material obtained in step S1 is molded, degummed, and fired to obtain ceramic tiles made from the waste material.

[0007] Preferably, the method for preparing the gel particles in step S1 comprises: Ammonium nitrate, cellulose nanofibers, graphene oxide dispersion and ascorbic acid are mixed, heated and dried, sintered and ground to obtain gel particles.

[0008] Preferably, the weight ratio of the ammonium nitrate, the cellulose nanofibers, the graphene oxide dispersion and the ascorbic acid is 1:1:2:2.

[0009] Preferably, the method for preparing the precursor material in step S2 includes: Under a nitrogen atmosphere, ferrous sulfate, manganese sulfate, sodium ethylenediaminetetraacetate and water are mixed and stirred for 2-4 hours, and then oxalic acid is added, and the reaction is continued by stirring for 12-24 hours, and then dried to obtain a nano precursor.

[0010] Preferably, the weight ratio of ferrous sulfate, manganese sulfate, sodium ethylenediaminetetraacetate, water and oxalic acid is 1:1:2:5:1.

[0011] Preferably, the heating temperature is 80-100° C., and the heating time is 1-2 hours; the drying temperature is 40-60° C., and the drying time is 12-24 hours.

[0012] Preferably, the sintering atmosphere includes oxygen-containing nitrogen; the volume proportion of oxygen in the oxygen-containing nitrogen is 1%; the sintering temperature is 500-700° C.; and the sintering time is 2-3 hours.

[0013] Preferably, the molding, degumming and sintering of the molding material in step S2 specifically includes: The molding temperature is 300-400° C., the molding pressure is 5-6Mpa, and the molding time is 8-10s; the degumming temperature is 600-700° C.; the sintering temperature is 1500-1540° C., and the time is 10-12h.

[0014] The present invention constructs a porous skeleton structure through gel particles and precursor materials. The carbon nanofibers further act as a three-dimensional nano-support skeleton in the porous skeleton structure to prevent agglomeration between components. At the same time, the carbon nanofibers superimposed on the porous skeleton structure can increase the specific surface area and contact area between the components. The component materials are filled in the pores of the porous skeleton structure to reduce the component gaps, improve the ceramic bonding force and density, thereby eliminating defects between components, reducing stress concentration points, and improving mechanical properties. DETAILED DESCRIPTION

[0015] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In addition, it is specifically stated that the raw materials and equipment of the present invention can be obtained from commercial sources, and no longer listed one by one. Among them, the raw materials of the present invention can be obtained from commercial sources and are well known to those skilled in the art. Embodiment 1:

[0016] A ceramic tile made from waste materials comprises the following components in parts by weight: 20 parts of waste ceramic pieces, 30 parts of gel particles, 10 parts of precursor materials, 5 parts of carbon nanofibers, 6 parts of magnesium oxide, 10 parts of sodium hydroxymethyl cellulose, 10 parts of coal slag and 18 parts of kaolin.

[0017] A method for preparing ceramic tiles made from waste materials comprises the following steps: S1: Mix the above-mentioned waste ceramic pieces, gel particles, precursor materials, carbon nanofibers, magnesium oxide, binder, coal slag and kaolin in parts by weight, and ball-mill through a 200-mesh sieve to obtain a mixture; S2: The mixture obtained in step S1 is molded, degummed and fired. The molding temperature is 300°C, the molding pressure is 5Mpa, and the molding time is 8s; the degumming temperature is 600°C; the firing temperature is 1500°C, and the time is 10h to obtain ceramic tiles.

[0018] Among them, the preparation method of gel particles in step S1 includes: mixing ammonium nitrate, cellulose nanofibers, graphene oxide dispersion with a concentration of 0.5 g / L and ascorbic acid in a weight ratio of 1:1:2:2, heating and drying, the heating temperature is 80°C, the heating time is 1 hour; the drying temperature is -40°C, the drying time is 12 hours, and sintering treatment, the sintering treatment atmosphere includes oxygen-containing nitrogen; the volume proportion of oxygen in the oxygen-containing nitrogen is 1%; the sintering treatment temperature is 500°C; the sintering time is 2 hours, and grinding is performed to obtain gel particles.

[0019] The method for preparing the precursor material in step S2 includes: Under a nitrogen atmosphere, ferrous sulfate, manganese sulfate, sodium ethylenediaminetetraacetate and water were mixed and stirred for 2 hours, and then oxalic acid was added. The reaction was continued with stirring for 12 hours and dried to obtain a nano precursor, wherein the weight ratio of ferrous sulfate, manganese sulfate, sodium ethylenediaminetetraacetate, water and oxalic acid was 1:1:2:5:1. Embodiment 2:

[0020] A ceramic tile made from waste materials comprises the following components in parts by weight: 30 parts of waste ceramic pieces, 40 parts of gel particles, 20 parts of precursor materials, 8 parts of carbon nanofibers, 8 parts of magnesium oxide, 12 parts of sodium hydroxymethyl cellulose, 15 parts of coal slag and 20 parts of kaolin.

[0021] A method for preparing ceramic tiles made from waste materials comprises the following steps: S1: Mix the above-mentioned waste ceramic pieces, gel particles, precursor materials, carbon nanofibers, magnesium oxide, binder, coal slag and kaolin in parts by weight, and ball-mill through a 200-mesh sieve to obtain a mixture; S2: The mixture obtained in step S1 is molded, degummed and fired. The molding temperature is 400°C, the molding pressure is 6Mpa, and the molding time is 10s; the degumming temperature is 700°C; the firing temperature is 1540°C, and the time is 12h to obtain ceramic tiles.

[0022] Among them, the preparation method of gel particles in step S1 includes: mixing ammonium nitrate, cellulose nanofibers, a graphene oxide dispersion with a concentration of 0.5 g / L and ascorbic acid in a weight ratio of 1:1:2:2, heating and drying, the heating temperature is 100°C, and the heating time is 2h; the drying temperature is -60°C, the drying time is 24h, and sintering treatment, the sintering treatment atmosphere includes oxygen-containing nitrogen; the volume proportion of oxygen in the oxygen-containing nitrogen is 1%; the sintering treatment temperature is 700°C; the sintering time is 3h, and grinding is performed to obtain gel particles.

[0023] The method for preparing the precursor material in step S2 includes: Under a nitrogen atmosphere, ferrous sulfate, manganese sulfate, sodium ethylenediaminetetraacetate and water were mixed and stirred for 4 hours, and then oxalic acid was added. The reaction was continued with stirring for 24 hours and dried to obtain a nano precursor, wherein the weight ratio of ferrous sulfate, manganese sulfate, sodium ethylenediaminetetraacetate, water and oxalic acid was 1:1:2:5:1. Embodiment 3:

[0024] A ceramic tile made from waste materials comprises the following components in parts by weight: 25 parts of waste ceramic pieces, 35 parts of gel particles, 15 parts of precursor materials, 6 parts of carbon nanofibers, 7 parts of magnesium oxide, 11 parts of sodium hydroxymethyl cellulose, 12 parts of coal slag and 19 parts of kaolin.

[0025] A method for preparing ceramic tiles made from waste materials comprises the following steps: S1: Mix the above-mentioned waste ceramic pieces, gel particles, precursor materials, carbon nanofibers, magnesium oxide, binder, coal slag and kaolin in parts by weight, and ball-mill through a 200-mesh sieve to obtain a mixture; S2: The mixture obtained in step S1 is molded, degummed and fired. The molding temperature is 350°C, the molding pressure is 5.5Mpa, and the molding time is 9s; the degumming temperature is 650°C; the firing temperature is 1520°C, and the time is 11h to obtain ceramic tiles.

[0026] Among them, the preparation method of gel particles in step S1 includes: mixing ammonium nitrate, cellulose nanofibers, a graphene oxide dispersion with a concentration of 0.5 g / L and ascorbic acid in a weight ratio of 1:1:2:2, heating and drying, the heating temperature is 90°C, and the heating time is 1.5 hours; the drying temperature is -50°C, the drying time is 18 hours, and sintering treatment, the sintering treatment atmosphere includes oxygen-containing nitrogen; the volume proportion of oxygen in the oxygen-containing nitrogen is 1%; the sintering treatment temperature is 600°C; the sintering time is 2.5 hours, and grinding to obtain gel particles.

[0027] The method for preparing the precursor material in step S2 includes: Under a nitrogen atmosphere, ferrous sulfate, manganese sulfate, sodium ethylenediaminetetraacetate and water were mixed and stirred for 3 hours, and then oxalic acid was added. The reaction was continued with stirring for 18 hours and dried to obtain a nano precursor, wherein the weight ratio of ferrous sulfate, manganese sulfate, sodium ethylenediaminetetraacetate, water and oxalic acid was 1:1:2:5:1. Comparative Example 1:

[0028] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that no gel particles and precursor materials are used, specifically: A ceramic tile made from waste materials comprises the following components in parts by weight: 20 parts of waste ceramic pieces, 5 parts of carbon nanofibers, 6 parts of magnesium oxide, 10 parts of sodium hydroxymethyl cellulose, 10 parts of coal slag and 18 parts of kaolin.

[0029] A method for preparing ceramic tiles made from waste materials comprises the following steps: S1: Mix the above-mentioned waste ceramic sheets, carbon nanofibers, magnesium oxide, binder, coal slag and kaolin in parts by weight, and ball-mill through a 200-mesh sieve to obtain a mixture; S2: The mixture obtained in step S1 is molded, degummed and fired. The molding temperature is 300°C, the molding pressure is 5Mpa, and the molding time is 8s; the degumming temperature is 600°C; the firing temperature is 1500°C, and the time is 10h to obtain ceramic tiles.

[0030] The following is a performance test of the ceramic tiles obtained in Examples 1 to 3 of the present invention, Comparative Example 1, and ordinary ceramic tiles (purchased from Jingdezhen Welland Ceramics Co., Ltd.), and the test results are shown in Table 1.

[0031] The mechanical strength of ceramic tiles is tested in accordance with GB / T 4740-1999.

[0032] Table 1 Test data of Examples 1-3, commercially available ceramics and Comparative Example 1 It can be seen from the above table that the mechanical properties of Examples 1-3 are improved compared with those of Comparative Example 1 and commercially available ceramics, and they have good compressive strength, fracture toughness and flexural strength.

[0033] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A ceramic tile made from waste materials, characterized in that: The invention comprises the following components in parts by weight: 20-30 parts of waste ceramic sheets, 30-40 parts of gel particles, 10-20 parts of precursor materials, 5-8 parts of carbon nanofibers, 6-8 parts of magnesium oxide, 10-12 parts of binder, 10-15 parts of coal slag and 18-20 parts of kaolin.

2. The ceramic tile made from waste materials as claimed in claim 1, characterized in that: The binder is sodium hydroxymethyl cellulose.

3. A method for preparing ceramic tiles made from waste materials as claimed in claim 1, characterized in that: The following steps are involved: S1: Mix the waste ceramic pieces, gel particles, precursor materials, carbon nanofibers, magnesium oxide, binder, coal slag and kaolin, and ball-mill them through a 200-mesh sieve to obtain a mixture; S2: The mixed material obtained in step S1 is molded, degummed, and fired to obtain ceramic tiles made from the waste material.

4. The method for preparing ceramic tiles using waste materials as claimed in claim 3, characterized in that: The method for preparing the gel particles in step S1 comprises: Ammonium nitrate, cellulose nanofibers, graphene oxide dispersion and ascorbic acid are mixed, heated and dried, sintered and ground to obtain gel particles.

5. The method for preparing ceramic tiles using waste materials as claimed in claim 4, characterized in that: The weight ratio of the ammonium nitrate, the cellulose nanofibers, the graphene oxide dispersion and the ascorbic acid is 1:1:2:

2.

6. The method for preparing ceramic tiles using waste materials as claimed in claim 3, characterized in that: The method for preparing the precursor material in step S2 includes: Under a nitrogen atmosphere, ferrous sulfate, manganese sulfate, sodium ethylenediaminetetraacetate and water are mixed and stirred for 2-4 hours, and then oxalic acid is added, and the reaction is continued by stirring for 12-24 hours, and then dried to obtain a nano precursor.

7. The method for preparing ceramic tiles using waste materials as claimed in claim 6, characterized in that: The weight ratio of the ferrous sulfate, manganese sulfate, sodium ethylenediaminetetraacetate, water and oxalic acid is 1:1:2:5:

1.

8. The method for preparing ceramic tiles using waste materials as claimed in claim 4, characterized in that: The heating temperature is 80-100° C., and the heating time is 1-2 hours; the drying temperature is -40--60° C., and the drying time is 12-24 hours.

9. The method for preparing ceramic tiles using waste materials as claimed in claim 4, characterized in that: The sintering atmosphere includes oxygen-containing nitrogen; the volume proportion of oxygen in the oxygen-containing nitrogen is 1%; the sintering temperature is 500-700° C.; and the sintering time is 2-3 hours.

10. The method for preparing ceramic tiles using waste materials as claimed in claim 3, characterized in that: The step S2 of molding, degumming and sintering the molding material specifically includes: The molding temperature is 300-400° C., the molding pressure is 5-6Mpa, and the molding time is 8-10s; the degumming temperature is 600-700° C.; the sintering temperature is 1500-1540° C., and the time is 10-12h.

Citation Information

Patent Citations

  • Special coal cinder for preparing porcelain tile

    CN104496412A

  • Processing technology for porcelain tile

    CN104496413A

  • Novel environment-friendly energy-saving fireproof building material and preparation method thereof

    CN108484025A

  • High-temperature-resistant ceramic for buildings and preparation method of high-temperature-resistant ceramic

    CN108947479A

  • High-strength and high-whiteness ceramic product and processing technology thereof

    CN114477951A

Cited By

  • Process for preparing ceramic tile by dry method

    CN121021123A

  • A process for the dry preparation of ceramic tiles

    CN121021123B